Pharmacognostical Study and Isolation of Terpene of Iraqi Quisqualis Indica L. - Thamer Mouhi Jasiem (Journal of Global Pharma Technology, 2018)
Quisqualis indica L. has been used in traditional medicine for treatment many diseases .Q. indica containing many of secondary metabolite products like tannins, flavonoids, steroids, carbohydrates, protein, amino acids, saponins and phenolic compounds .The leaves of plant Q. indica L. were collected from AL-Musaeeb city , for phytochemical screening we used ethanolic extract of plant leaves with standard methods of phytochemical tests .In microscopically study of Q. indica leaves both fresh and dried as finely powdered . Determination of the components of leaves was observed under microscope. The microscopical examination results were referred to anomocytic type of stomata at upper and lower surface of leaves. Unicellular UN branched covering of trichomes with fibers, Calcium oxalate with starch grain and stone cells were presented. The GC-MS analyses of hexane extract of leaves were carried out identification of Methyl palmitate 10.4%, Methyl linolate 8.6%, Trans – squalene 5.1%, Tetratetracontane 7.1% and Heptacosane-1-chloro 7.9%. Phytochemically, Iraqi plant contains tannins, flavonoids, terpene, coumarin and saponins, while alkaloid, steroids may be absent or present as a minor constituent. Which indicates that the Iraqi plant have some medicinal properties.Keywords: Quisqualis indica, Phytochemical study, GC/MS analysis, Pharmacognostical study.